Following the agenda of others: IOC communication in the Olympic postponement - Almeida, W.; Freitas, R.; Rubio, K.; Mendonça, E. (Olimpianos - Journal of Olympic Studies, 2020)
World news in the first three months of 2020 was dominated by information about the progress of the pandemic caused by COVID-19. The theme left the pages dedicated to health and invaded the news in all the editorials. As the disease progressed around the world, the International Olympic Committee, in a posture of isolation, maintained its media channels with information on the preparation for the Tokyo Olympic Games, initially planned for 2020, as if the disease was not related to the Olympic movement. The attempt to maintain a parallel agenda, however, was overcome by the facts and the interest of the traditional media in reporting on the feasibility of holding a worldwide event during a pandemic. This article analyzes two official IOC channels - the entity's official portal and the Twitter profile, and discusses, based on the scheduling theory, the position adopted by the entity. Based on the data collected, it was possible to observe that the COI, while ignoring COVID-19 for a long time, opened space for the media to guide the debate and to report private information about the COI even before the official channels of the entity.